ADVANTAGES OF DENTAL DISPENSARY SERVICE GROUP DECREED INDUSTRIAL WORKERS - V. N. Olesova; T. N. Novozemtseva; A. Y. Lerner; E. E. Olesov; A. A. Remizova (Кубанский научный медицинский вестник)
The article analyzes the results of dental examination of employees to hazardous and normal working conditions at the company Atomenergomash based on the previous organization of dental care; provided clear evidence of the effectiveness of outpatient care workers in terms of reduction in the dental treatment needs. It was found that the dispensary method of dental care with an annual treatment of dental and periodontal provides a significant reduction in the intensity of dental diseases and the need for dental treatment of patients with hazardous working conditions of workers. At clinical examination prevails therapeutic and preventive effects on periodontium. The need for replacement of dental hard tissue defects and endodontic treatment 2 times less, replacing the seals and audit root canal - 4 times.